Protracted severe systemic cytomegalovirus disease in an immunosuppressed patient with ulcerative colitis. Issue 2 (29th September 2017) - Armstrong, Matthew James; Thomas, Tom; Iqbal, Tariq; Boulton, Ralph; Goh, Jason
Abstract : A 33-year-old man with ulcerative colitis presented with 5-day history of fever, night sweats, abdominal pain and increased stool frequency. He was on mesalazine M/R 1 g once daily, 6-mercaptopurine (6-MP) 75 mg once daily and prednisolone 40 mg once daily. Examination revealed fever and tachycardia. Blood examinations identified a persistent leucopenia, C reactive protein of 23 mg/L and an initial alanine transaminase of 855 IU/L. Flexible sigmoidoscopy revealed well-demarcated, punched-out ulcers in the proximal rectum and distal sigmoid, with histology pathognomonic of cytomegalovirus (CMV). CMV DNA PCR was 51 140 copies/mL. Despite prompt withdrawal of 6-MP, steroids and initiation of intravenous ganciclovir on day 2 of admission, his systemic illness, diarrhoea and fever persisted until day 19 of antiviral therapy. Other copathogens and lymphoma were ruled out on serology and CT scan, respectively. After an unusually prolonged course of antiviral therapy, the patient made a full clinical recovery, bloods normalised and there were two consecutive undetectable CMV DNA PCRs.